2008
DOI: 10.1111/j.1751-7133.2008.07827.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Degradation and Left Bundle Branch Block Predict Conversion to Low Ejection Fraction in Heart Failure With Preserved Systolic Function

Abstract: The authors prospectively investigated whether left bundle branch block (LBBB) and myocardial degradation as indicated by elevated troponin T (tnT) predict the phenomenon of systolic conversion to low ejection fraction (EF 40%). Thirty consecutive patients with HFPSF were included and followed over a 4-year interval. A follow-up EF assessment was performed in 25 patients. Six of 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…EF deterioration to values ≤40% was associated in our cohort with history of CHF diagnosed prior to the baseline echocardiogram. Several studies have demonstrated a link between interventricular dyssynchrony and LV function dysfunction . In a study investigating patients with CHF and baseline normal systolic function, we were able to demonstrate a significant LVEF drop in the subgroup with LBBB in contrast to the patients without this conduction anomaly .…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…EF deterioration to values ≤40% was associated in our cohort with history of CHF diagnosed prior to the baseline echocardiogram. Several studies have demonstrated a link between interventricular dyssynchrony and LV function dysfunction . In a study investigating patients with CHF and baseline normal systolic function, we were able to demonstrate a significant LVEF drop in the subgroup with LBBB in contrast to the patients without this conduction anomaly .…”
Section: Discussionmentioning
confidence: 49%
“…Several studies have demonstrated a link between interventricular dyssynchrony and LV function dysfunction. 2,9 In a study investigating patients with CHF and baseline normal systolic function, we were able to demonstrate a significant LVEF drop in the subgroup with LBBB in contrast to the patients without this conduction anomaly. 2 Interestingly, in the current study, admissions for CHF with preserved EF as well as cardiac admissions were more frequent in patients prone to EF deterioration, stressing the importance of this phenomenon.…”
Section: Etiology Of Ef Deterioration To Values 40%mentioning
confidence: 78%
See 2 more Smart Citations
“…New-onset LBBB leading to poor prognosis (even in asymptomatic patients) rises several questions concerning the importance of assessing relationship between this arrhythmic phenomenon and other functional and structural cardiac deterioration such as cardiac ischemic events ( 1 ), left ventricular hypertrophy ( 2 ), heart failure state ( 3 ), and left ventricular dysfunction ( 4 ). In this regard, the deleterious impact of LBBB on left ventricular systolic and diastolic function has been established even in patients without overt underlying heart disease ( 5 ).…”
Section: Introductionmentioning
confidence: 99%